2016
DOI: 10.14295/cs.v7i3.1258
|View full text |Cite
|
Sign up to set email alerts
|

Comportamento de genótipos de maturação precoce de cana-de-açúcar na Zona da Mata de Pernambuco

Abstract: No cultivo comercial da cana-de-açúcar, conhecimentos relacionados ao desempenho de genótipos em diferentes épocas de colheita, são essenciais na identificação daqueles que se destacam quanto à precocidade, que sendo selecionados, contribuirão para o aumento da produtividade agroindustrial. Objetivou-se com este trabalho avaliar o desempenho agroindustrial de 26 genótipos de cana-de-açúcar e selecionar os que se destacaram quanto à maturação precoce para colheita em início de safra. Os experimentos foram condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
1
0
0
1
Order By: Relevance
“…Silva et al (2014), observed the same evidences when evaluating the production of different sugarcane varieties during two cycles under fully drip irrigation and besides these, identified differences in TPH responses due to the genetic distinction, thus, highlighted that RB855536 is less productive when compared to SP85-1115, IACSP96-3060, RB867515 and IAC91-1099 cultivars. Albuquerque et al (2016) also verified similar, differences between the genotypes for TCH and TPH characters, associating these results to the genetic variability and not to the production environmental issues.…”
Section: Resultssupporting
confidence: 70%
“…Silva et al (2014), observed the same evidences when evaluating the production of different sugarcane varieties during two cycles under fully drip irrigation and besides these, identified differences in TPH responses due to the genetic distinction, thus, highlighted that RB855536 is less productive when compared to SP85-1115, IACSP96-3060, RB867515 and IAC91-1099 cultivars. Albuquerque et al (2016) also verified similar, differences between the genotypes for TCH and TPH characters, associating these results to the genetic variability and not to the production environmental issues.…”
Section: Resultssupporting
confidence: 70%
“…Os altos valores do coeficiente de determinação genotípico é um indicativo de sucesso na seleção com perspectivas favoráveis de ganhos genéticos através da recombinação das variedades em trabalhos de hibridação, conforme destacado por Albuquerque et al (2016). Os altos valores do coeficiente de determinação genotípico revelam uma alta probabilidade do potencial genético dessas variedades com relação à resposta a adubação nitrogenada serem transmitidas às suas progênies em trabalhos de hibridação.…”
Section: Variáveisunclassified